Review of Jennifer Mara Desilva, ed., The Sacralization of Space and Behavior in the Early Modern World: Studies and Sources - Dialeti, Androniki (Historein, 2017)
Jennifer Mara DeSilva, ed. The Sacralization of Space and Behavior in the Early Modern World: Studies and Sources. Burlington: Ashgate, 2015. viii + 326 pp.